KEUNGGULAN KOMPARATIF-KOMPETITIF DAN STRATEGI KEMITRAAN - -, SAPTANA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008, 2012)
Change of strategic environment in the form of economic globalization, decentralization, change of consumer preference and sustainability of environment, claiming the existence of change and also adjustment operate institution of agriculture. This article is addressed to study status comparative and competitive advantage some agriculture commodities, partner of business agriculture performance, and revitalization institution of agriculture to realize comparative advantage become competitive advantage through partner business strategy. Status comparative and competitive advantages show though most agriculture commodities till in this time remain to have comparative and competitive advantage, but advantages had progressively lower and rentan to change of external, with coefficient value of DRCR and of PCR come near number 1 (one). Until so far not yet been woke up by institution partner of business which each other requiring, each other strengthening, and each other profiting, and also the nature of partner which do not have sustainable. Several weakness for example is lowering him of commitment among which was have partner, position bargaining not equality, and also less him in pricing and division of added value or profit margin. Institution partnership of business agriculture conducting consolidation farm group; level of self-supporting farmer group up at formal institution (co-operation of association) and revitalization institute of counseling up at Center Service and Consultancy of Agribusiness, which one of the function are mediator and facilitator. With expected inwrought effort partner strategy can realize comparative advantage become competitive advantage either in local market, exporting and regional.
Keywords: Comparative Advantage, Competitive Advantage, and Partner of Business